Effectiveness of Aromatherapy on Lowering Blood Pressure of Preeclampsia Mother During Conservative Treatment - Yenny Puspitasari; Reni Nurhidayah; Katmini Katmini (Sekolah Tinggi Ilmu Kesehatan Kendal, 2022)
Preeclampsia is still a pregnancy complication that causes the third-highest maternal mortality in Indonesia. The focus of conservative care is to maintain blood pressure to delay termination of pregnancy as optimally as possible. Aromatherapy has the potential to lower blood pressure and improve sleep quality in preeclampsia. The purpose of this study was to determine the effect of aromatherapy on reducing blood pressure and improving sleep quality. The design used in this study is a quasi-experimental study with a pretest-posttest control group design. Respondents in this study were 60 preeclampsia mothers in the treatment room of RSUD dr. Soetomo during the months of February to September that randomly assigned to the treatment and control groups. The sampling technique used is purposive sampling. Aromatherapy (lavender, ylang-ylang, and bergamot) was conducted for three consecutive days. A sphygmomanometer was used to measure blood pressure. Paired sample and unpairesd sample t-test were used for data analysis. There was a significant difference in systolic and diastolic blood pressure between the intervention and control groups with systolic p-value = 0.010 and diastolic p-value = 0.021. There is an effect of lavender, ylang-ylang, and bergamot aromatherapy on reducing blood pressure in preeclamptic mothers during conservative treatment.